Resonance phenomena of an elastic ring under a moving load - Forbes, Gareth; Randall, R. (ELSEVIER, 2008)
This study investigates the response of a circular ring under a moving load. Past work on shells under the influence of moving loads is consolidated, with explanation of the formation of the unique quasi-stationary mode shapes, which are seen under these conditions. This work presents an alternate method of solution for problems for which moving loads are present and encourages distinguishing between normal mode shape methods and the solution methods for the proposed quasi-stationary resonance problems. This alternate method is then followed through to a general solution for quasi-stationary mode shapes, with specific solutions presented for the following three cases: magnitude-varying moving point load, phase varying moving point load and a non-uniform continuous moving load, all applied to a stationary ring.